‘Danger: Children at Play’: Uncanny Play in Stephen King’s Pet Sematary - Krista Collier-Jarvis (Humanities, 2023)
Representations of play abound in Stephen King’s 1983 novel Pet Sematary and its 1989 and 2019 subsequent film adaptations. However, play in Pet Sematary is not representative of the innocent actions designed to create functioning adults who meaningfully contribute to society. In the 1989 film, for example, “play” for a newly resurrected Gage is a version of hide-and-go-seek resulting in the death of neighbour Jud. Meanwhile, the 2019 adaptation sees a newly resurrected Ellie “playing” in her dirt-stained white funereal dress. These dirt stains become markers of lost innocence and transform her dance into an uncanny performance. Since Gage and Ellie are both somewhat monstrous child figures, their play, like their bodies, is transformed into something unsettling and ventures into the realm of the uncanny. However, play itself is also performed differently between the adaptations because the central child figure also changes. In the 1989 film, it is a male toddler, and in the 2019 film, it is a pre-pubescent female. Both adaptations focus on ideal, socially acceptable forms of play according to the time in which the film was made as well as how children diverge from these behaviours. Play is often rendered dangerous when not performed properly according to the paradigms of age and gender, resulting in what I call ‘uncanny play’. When children engage with ‘uncanny play’, the adults in the narrative are permitted to execute the children for the sake of preserving the memory of them as innocent beings, or what I call the ‘Save the Child’ discourse. Linda Hutcheon argues that ‘when we adapt […] we actualize or concretize ideas’, so that the socially acceptable play put forth in King’s novel becomes more realised and thus more at risk to transgression in each successive filmic adaptation.